Influence Of Water Absorption On The Mechanical Properties Of Jute Fibre Bio-Composite - Doraisamy, Hemarajan (Universiti Sains Malaysia, 2021)
Bio-composites are increasingly viewed as a renewable alternative to synthetic composites in many applications. However, low durability and rapid degradation of biocomposites in outdoor applications have become a major problem. In particular, wet environments can cause a rapid deterioration in the mechanical properties and efficiency of bio-composites due to moisture absorption. The focus of this work has been to study the mechanical properties of jute fibre bio-composite with and without the influence of water absorption. Distilled water was used to environmentally age the bio-composite samples using the immersion bath technique at room temperature. The studied composite materials used polyester resin as the matrix and were manufactured using wet hand lay-up process. Tensile test and flexural test were conducted on the saturated samples after being immersed for 36.7 hours0.5 and 32.6 hours0.5, respectively. The tensile test was carried out based on ASTM D 3039 standard, while the flexural test was conducted based on ASTM D 7264 standard. All of the sorption behaviours obtained display a classic Fickian sorption curve. A significant decrement in the mechanical properties of the saturated samples was observed when compared to the standard samples. A reduction of 56.8% in tensile strength, 55.0% in tensile modulus, 31.7% in flexural strength and 47.7% in flexural modulus was shown. This study showed that jute-fibre composites are not suitable for applications in a humid environment, and further modification is needed to improve their moisture absorption properties.